IMPLEMENTASI VPN UNTUK PENGENDALI JARAK JAUH SERVER MELALUI PERANGKAT ANDROID PADA JARINGAN KOMPUTER SMK TRIATMA JAYA SEMARANG (Information Technology and Telematics, 2015)
Abstract – The development of computer technology that is very  rapidly, makes enterprises and educational institutions to implement the functions of the computer technology for many purposes. Comparable with increasing functionality of computer technology , the need for extensive computer networks is required so that each member of the enterprise can use the services provided by technology. The need for local network access capabilities of the network beyond the scope of the school is required by Triatma Jaya Semarang Senior High School to facilitate the network administrator to configure the server and the School’s administrator as well as the teachers in the school to access files on the school’s server. These problems can be overcome by using the technology of Virtual Private Network (VPN) that provides connection services between computer networks privately and securely . Meanwhile, to meet the need for flexibility and ease of access to the local network , it makes the mobile device as a choice to be used as a VPN client on the connection . which is of course highly dependent on the quality of the internet connection which is used by the android device. Keywords - VPN, Virtual Privat Network, android, jaringan komputer, servr.